Conversion of Waste Engine Oil to Gasoline and Diesel Range Fractions by Thermal Treatment - Prof. Ashok L. Rathod; Mr. Krushna C. Mehatre; Mr. Rushikesh V. Shedge (International Journal of Scientific Research in Science and Technology, 2025)
The disposal of waste engine oil possesses significant environmental and economic challenges. The study investigates the potential of thermal treatment as a sustainable method for cracking of waste engine oil into valuable diesel and gasoline range fractions. Through experimental analysis the key parameters such as temperature, feed flowrate are optimized to enhance product yield and product quality. The purpose of thermal treatment of waste engine oil is to determine whether the procedure is appropriate for extracting valuable fractions from waste engine oil, otherwise its challenge to dispose of the waste engine oil. After treatment the cracked gases were condensed into liquid fractions, the yield and properties of recovered fractions is determined. It is possible to use the recovered cracked liquid or gaseous fraction as a feed stock for chemical industry or as a valuable blend stock for fuel. The finding suggest that thermal treatment has great potential as a way to get rid of waste engine oil that causes environmental and ecological hazards. The conversation of waste engine oil into diesel and gasoline fraction has been undertaken in this work. In this work numerous details on the harmful nature of waste engine oil and their impact on environment are also included.
Keywords: API; ASTM; Waste Engine Oil; Thermal Treatment; Diesel and Gasoline Fractions